Evaluación del comportamiento de los indicadores físico químicos, sensoriales, microbiológicos y de aceptación de la Bebida Isotónica preparada a partir del jugo natural de Naranja estandarizada durante su almacenamiento. - Iza Carrión, Johana Belén (2020)
The objective of the research work proposal was to evaluate the behavior of the physical chemical, sensory, microbiological and acceptance indicators of the isotonic drink prepared from orange juice (Citrus x sinensis), the development of the research it was investigated in academic search engines: scientific articles, articles in scientific journals, degree work done. After the bibliographic analysis of four methodologies for the preparation of isotonic drinks, it was considered to extract essential points to carry out the research proposal of an isotonic drink indicating the use of orange juice (Citrus x sinensis). A review of the minimum quality control parameters was also carried out in the reception of the raw material, such as: maturity criteria (maturity index, classification by size) and minimum juice or juice content (30%), considering a quality raw material guaranteeing safety within the elaboration of the isotonic drink. In this case, to make the isotonic drink, it is recommended to use the Valencia orange variety due to its high juice content, which in turn has a high production in Ecuador. The requirements for the preparation of the drink were specified where the physical-chemical parameters were established such as: pH (3.3 - 4.0), titratable acidity (0.3 - 0.7), degrees ° Brix (11.0), sodium (10-20 mEq / L), potassium (2.5-5 mEq / L), chloride (10-12 mEq / L) and osmorality (200 - 420 mOsm / L), microbiological requirements: count of aerobic mesophilic microorganisms / ml, MPN Coliforms / ml, MPN Coliforms fecal / ml) and sensory, which propose a descriptive method to evaluate according to a hedonic scale with values from 1 to 5 (color, smell, taste and acceptability) of the isotonic drink according to the Colombian Technical Standard (NTC COLOMBIANA 3837, 2009) matching these indicators to obtain the isotonic drink to be made. In the evaluation proposal, the influence of its physical-chemical, microbiological, nutritional and sensory characteristics of the elaborated product is disclosed, making known the benefits that said drink provides to potential future consumers